ANALISIS ISYTIQAQ DALAM KAJIAN FIKIH LUGHAH DAN PENGAJARANNYA - DEVY AISYAH (Ta'dib, 2015)
The study of Istisqaq (derivational word) as a part of Fiqh lughah (Arabic linguistic) is a main concern of linguists in the recent decade. Istisqa’ is one of the distinguished features of Arabic which have rich vocabulary. In the early of the third century of Hijriah year, several Ulamas (Moslem scholar) pay a serious attention in the study of Istisqaq. Istisqaq is a process of forming a word to another word in order to produce a new meaning. This formation was initiated by Ibn Jinniy. He then wrote a monumental book entitled Al-Khashaish. Istisqaq is identical with the study of Ilm Syarf (morphology).  This paper concludes that the teaching of fiqh lughah in an advanced level needs to improve. In addition to this, the addition of language structure could be taught contextually and communicatively.   Kata kunci: analisis, isytiqaq, fikih lughah